Implementation of fuzzy logic in autonomous irrigation system for efficient use of water - Haque, Mohammad Mahbubul; Khan, Mahbubur Rahman; Ruhi, Raihana Ismat; Hasan, Md. Fuad (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.